Turkey : Report on the Observance of Standards and Codes-Data Module; Response by the Authorities, and Detailed Assessments Using the Data Quality Assessment Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Report on the Observance of Standards and Codes provides a review of Turkey's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS) complemented by an in-depth assessment of the quality of the national accounts, consumer and producer price indices, government finance, monetary, and balance-of-payments statistics. The findings reveal that Turkey subscribes to the SDDS. Turkish statistical agencies in the main have a legal and institutional framework that supports statistical quality. Agencies demonstrate an awareness of quality as the cornerstone of statistical work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet